CHALLENGES OF TEACHING AND LEARNING ENGLISH ONLINE DURING THE COVID-19 PANDEMIC AT SMK NEGERI 1 BARUMUN KABUPATEN PADANG LAWAS - Rima Nurcahya; Hadriana Hadriana; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Covid-19 is an infectious disease caused by a type of corona virus that was newly discovered in the city of Wuhan, China (WHO, 2020). As a result, all activities can only be carried out on a limited basis, and places that cause crowds are closed, including schools. So that learning and teaching activities are carried out online or in other words learning from home. The purpose of this research were to find out what challenges faced by teachers and students when learning takes place online, as well as to identify or find out the efforts made by teachers at SMK Negeri 1 Barumun to overcome these challenges. The research method used in this research was descriptive qualitative with a case study approach. The data collection techniques used were interviews and documentation, while the data analysis techniques used were data reduction, data display, and withdrawal and conclusion verification. Based on this research, the results obtained are the challenges faced by English teachers at SMK Negeri 1 Barumun during online teaching are difficulties in increasing students’ motivation in learning English, teachers have challenges in choosing appropriate learning strategies, and lack of technology mastery skills. While the challenges faced by students are related to the instability of the internet network in the area they live, limited quotas, and limitations of android as the main online learning facility due to the family’s economic instability. Based on these challenges, teachers and school implemented several efforts to overcome these challenges with the aim that learning and teaching activities continue to run smoothly and effectively.Key Words: Covid-19 Pandemic, Online Teaching, Online Learning, English Online, andChallenges.